Method for preparing energy storage battery fabric through 3D printing
Through 3D printing technology, energy storage battery fabrics are prepared using composite polymers and nanoelectrode active materials, which solves the complexity and integration problems of fiber battery preparation, realizes high-performance flexible energy storage fabric manufacturing, and promotes its application to practical development. .
Patent Information
- Application Number
- CN202411282898.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-13
AI Technical Summary
The existing fiber battery preparation process is complicated, making it difficult to achieve large-scale preparation and high-density integrated energy storage fabrics, hindering their promotion in actual production and application.
Using 3D printing technology to prepare energy storage battery fabrics, through electrode fabric printing, gel electrolyte coating and polymer packaging, the properties of composite polymers, multi-wall carbon nanotubes and nanoelectrode active materials are used to achieve flexible and breathable energy storage fabrics. preparation.
The battery preparation process is simplified, mechanical properties and electrochemical reaction efficiency are improved, and high-performance energy storage fabric manufacturing is realized, providing a better implementation path for the market-oriented application of energy storage fabrics.
Smart Images

Figure CN119133622A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing energy storage battery fabric by 3D printing, belongs to the field of secondary batteries and their manufacture, and is used for conveniently manufacturing flexible energy storage battery fabric, realizing more wearable energy storage devices, and providing energy for wearable portable electronic devices. Background Art
[0002] In the development of fiber batteries, the assembly, packaging and fabric integration of fiber batteries are also huge challenges currently faced by fiber batteries. In the reported fiber battery research, the fiber battery was encapsulated in a heat shrink tube through a complex assembly process. Although this method has achieved laboratory-level testing and demonstration of fiber battery devices, the large-scale preparation of this method is very complicated and difficult to promote and achieve large-scale preparation. In addition, in the process from fiber batteries to fiber battery fabrics, given the current mechanical properties and size of fiber batteries, it is difficult to achieve higher density and high-performance integrated energy storage fabrics by integrating them into existing fabrics only by interlacing and weaving. These problems have seriously hindered the actual production and application of fiber batteries.
[0003] The use of 3D printing technology for fabric manufacturing has achieved many breakthroughs in clothing comfort design, thermal control, wearable sensing and medical fields. Taking advantage of its advantages in structural design and precision, 3D printing can prepare and assemble functional materials according to the designed fabric structure to achieve the functionalization of fabrics. This feature of 3D printing is applied to the preparation of fiber batteries and battery fabrics, realizing electrode fabric printing, electrolyte printing and coating, and polymer printing and packaging respectively. The direct preparation, assembly and packaging of battery fabrics in the form of fabrics is expected to greatly reduce the difficulties of assembly and integration currently faced in fiber electrodes, and realize the convenient preparation of flexible and breathable energy storage fabrics. Summary of the invention
[0004] (I) Purpose of the invention
[0005] The purpose of the present invention is to provide a method for preparing energy storage battery fabrics by 3D printing, so as to solve the technical problems that existing fiber batteries are difficult to prepare and difficult to integrate into energy storage fabrics.
[0006] (II) Technical solution
[0007] In order to achieve the above objectives and solve the above technical problems, the technical solutions of the present invention are as follows:
[0008] 1. A method for preparing energy storage battery fabric by 3D printing, characterized in that the method steps are as follows:
[0009] Step 1: Printing of electrode fabric
[0010] (1) Using a composite polymer, multi-walled carbon nanotubes and nano-electrode active materials, mixing them in a mass ratio of 1:1:2, adding a solvent 5 to 10 times the mass of the solid, grinding or ball milling to dissolve and evenly disperse them to obtain a slurry for printing electrodes;
[0011] The composite polymer is composed of a two-component polymer and a photoinitiator I2959, wherein component A is a photocurable polymer including polyethylene glycol diacrylate and polyethylene glycol dimethacrylate, and component B is a high-viscosity polymer that can be quickly physically cross-linked, including chitosan, sodium alginate and polyvinylidene fluoride; the mass of component A is 1 to 3 times the mass of component B;
[0012] The active material is lithium iron phosphate particles or lithium permanganate particles for the positive electrode, and lithium titanate particles or lithium titanium phosphate particles for the negative electrode;
[0013] The solvents used were deionized water for chitosan and sodium alginate and N-methylpyrrolidone for polyvinylidene fluoride;
[0014] (2) After the bubbles are removed by ultrasound, the slurry used for printing the electrode is placed in the syringe of an extrusion direct writing 3D printer and printed in a grid pattern. The distance between the grid lines in the printed pattern is greater than or equal to 4 mm, and the extrusion speed during the printing process is 1 to 2 mm 3 / s, the printing speed is 2~5mm / s;
[0015] (3) After printing, the copper and aluminum tabs are respectively inserted into the unshaped electrodes, and then immersed in a coagulation bath for 10 min until the polymer component B in the electrode is cross-linked and shaped, thereby obtaining positive electrode fabric and negative electrode fabric respectively;
[0016] Step 2: Printing and coating of gel electrolyte
[0017] (1) The components of the composite polymer in step 1 are also used, but the mass of component A is adjusted to 3 to 4 times the mass of component B, the solvent ratio is adjusted to 5 to 8 times the mass of the polymer, and lithium sulfate is added to a concentration of 1 to 2 mol / L. After the polymer and lithium sulfate are dissolved, vapor-deposited hydrophilic nano-silica with a mass of one-tenth of the polymer is added, and the mixture is mixed evenly in a ball mill to obtain a gel electrolyte precursor for printing;
[0018] (2) using a 3D printer to print the gel electrolyte precursor on both sides of the electrode fabric using the same printing pattern and parameters as the electrode fabric, so that the printed gel electrolyte can cover and wrap the electrode network. During the printing process of the gel electrolyte, the ultraviolet light with a wavelength of 365 nm is continuously irradiated to crosslink the electrode fabric and component A in the gel electrolyte;
[0019] (3) The printed preliminarily shaped gel electrolyte and the positive electrode fabric and the negative electrode fabric wrapped therein are combined and immersed in a 2 mol / L lithium sulfate coagulation bath for 10 min. Component B in the gel electrolyte is cross-linked to form a whole, and then washed with a 2 mol / L lithium sulfate solution;
[0020] Step 3: Printing and packaging of energy storage fabric
[0021] (1) Mixing photocurable polyurethane acrylate and 4% photoinitiator 1173, adding the same mass of polyethylene glycol acrylate monomer as solvent, stirring and removing bubbles, and then transferring into the syringe of a 3D printer;
[0022] (2) Set the printing extrusion speed to 2-3 mm 3 / s, the printing speed is 3-6mm / s, printing is performed on the front and back sides respectively, and ultraviolet light is irradiated during the printing process. The battery is encapsulated in the outer layer of the gel electrolyte to obtain an energy storage fabric.
[0023] Furthermore, the viscosity of the slurry used for printing electrodes is 10 2 ~10 4 Pa·s, and the viscosity decreases with increasing shear rate. In addition, the storage modulus is higher than the loss modulus under low shear stress. After exceeding a certain shear stress, the storage modulus is lower than the loss modulus.
[0024] Furthermore, the coagulation bath used is a solution that can cause component B in the composite polymer to undergo rapid physical crosslinking, such as a calcium chloride solution for chitosan or a sodium hydroxide solution for chitosan.
[0025] Furthermore, after printing the gel electrolyte and printing the encapsulated photocurable polymer, due to the rapid cross-linking and curing, after the polymer is wrapped, the polymer is prevented from further flowing and blocking the holes in the grid electrode fabric, and the air permeability of the fabric can be retained.
[0026] Furthermore, the prepared energy storage fabric has good flexibility due to the intrinsic flexibility of the electrodes, gel electrolyte and encapsulating polymer, and can maintain stable charge and discharge performance during bending.
[0027] (III) Effective income
[0028] The beneficial effects of the present invention are as follows: using 3D printing technology, the textile process of fabric forming is integrated into the preparation process of electrodes, electrolytes and packaging, so that the battery fabric is directly obtained by printing the electrode fabric, then printing and coating the gel electrolyte, and finally performing packaging printing, which greatly simplifies the preparation process and complexity, and avoids the stress and adverse effects of the weaving process on the battery material itself. In addition, the composition and processing requirements of the slurry used for printing ensure that the obtained battery has good mechanical properties and excellent internal electrochemical reactions and mass transfer processes, so that the battery fabric has good energy storage characteristics. This unique and novel manufacturing method and corresponding formula requirements can effectively improve the manufacturing level and application performance of energy storage fabrics, and provide a better implementation path for the development and market application of energy storage fabrics. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The structural schematic diagram of the energy storage battery fabric is printed;
[0030] In the figure: 1. Packaging material, 2. Positive electrode, 3. Negative electrode, 4. Gel electrolyte, 5. Energy storage battery fabric
[0031] Figure 2 Schematic diagram of the change of apparent viscosity of the slurry used for printing electrodes with shear rate;
[0032] In the figure: X-axis is shear velocity, unit is s -1 ; The Y-axis is the apparent viscosity, in Pa·s.
[0033] Figure 3 Schematic diagram of the change in modulus of the paste used for printing electrodes with oscillation strain;
[0034] In the figure: Curve 1 is the change of storage modulus; Curve 2 is a schematic diagram of the change of loss modulus;
[0035] The X-axis is the oscillation strain in %, and the Y-axis is the modulus in Pa. DETAILED DESCRIPTION
[0036] The present invention will be further described below in conjunction with the embodiments.
[0037] The preparation of battery fabrics is achieved through printing of electrode fabrics, printing and coating of electrolytes, and combining printing and packaging of polymers; the electrodes and electrolytes are stacked alternately, the positive and negative electrodes are wrapped by gel electrolytes and precisely assembled to form a fabric network, and photocurable polyurethane acrylate encapsulates the electrode fabric under mild conditions, demonstrating a new path for the preparation of flexible energy storage fabrics. This method has a simple process and is easy to implement. It provides a new idea for solving the difficulties faced by flexible energy storage fabrics and is expected to promote their further development towards practical application. In addition, this method has no literature or patent reports at home and abroad, and is innovative.
[0038] The technical solution adopted by the present invention is a method for preparing energy storage battery fabric by 3D printing. The steps are as follows: Figure 1 The battery fabric structure shown:
[0039] Step 1: Printing of electrode fabric
[0040] (1) Using a composite polymer, multi-walled carbon nanotubes and nano-electrode active materials, mixing them in a mass ratio of 1:1:2, adding a solvent 5 to 10 times the mass of the solid, grinding or ball milling to dissolve and evenly disperse them to obtain a slurry for printing electrodes;
[0041] The active materials in the electrodes are lithium iron phosphate particles and lithium permanganate particles for the positive electrode, and lithium titanate particles or lithium titanium phosphate particles for the negative electrode. These active materials have a relatively stable discharge platform and have a certain corrosion resistance to water and ethanol. Carbon nanotubes are used as conductive agents in the electrodes. Their elongated morphology at the microscopic level has an excellent match with the fiber electrode configuration, and can build a rich conductive network in the fiber, and play a certain skeleton support role for the electrode.
[0042] The composite polymer used in the electrode is composed of a two-component polymer and a photoinitiator I2959. Component A is a photocurable polymer, including polyethylene glycol diacrylate and polyethylene glycol dimethacrylate. These polymer components have good affinity and transmission effects on lithium salts, thereby constructing a good ion transmission channel in the electrode; component B is a high-viscosity polymer that can be quickly physically cross-linked, including chitosan, sodium alginate and polyvinylidene fluoride. This type of polymer can quickly form cross-links with a certain strength under certain induction, thereby ensuring the molding and mechanical strength of the electrode; the mass of component A is 1 to 3 times the mass of component B. Within this ratio range, the two polymers can work together to take into account good ion channels and mechanical properties;
[0043] The solvent used in the electrode slurry varies depending on the type of polymer used. When the polymer is chitosan or sodium alginate, the solvent is deionized water, and when the polymer is polyvinylidene fluoride, the solvent is N-methylpyrrolidone.
[0044] The slurry used to print electrodes needs to have specific rheological properties, specifically: viscosity between 10 2 ~10 4 Pa·s, and the viscosity decreases with increasing shear rate, such as Figure 2 As shown; in addition, the storage modulus is higher than the loss modulus under low shear stress, and after being subjected to a certain shear stress, the storage modulus is lower than the loss modulus, as shown Figure 3As shown; good rheological properties can ensure the continuity and smoothness of electrode printing, and maintain structural stability after printing and extrusion to avoid structural collapse and damage.
[0045] (2) After the bubbles are removed by ultrasound, the slurry used for printing the electrode is placed in the syringe of an extrusion direct writing 3D printer and printed in a grid pattern. The distance between the grid lines in the printed pattern is greater than or equal to 4 mm, and the extrusion speed during the printing process is 1 to 2 mm 3 / s, the printing speed is 2-5mm / s, and the appropriate spacing and printing and extrusion ratio can ensure the integrity and reliability of the structure of the printed electrode fabric, and reserve space for the printing of electrolyte and packaging materials;
[0046] (3) After printing, the copper and aluminum tabs are respectively inserted into the unshaped electrodes, and then immersed in a coagulation bath for 10 min until the polymer component B in the electrode is cross-linked and shaped, thereby obtaining positive electrode fabric and negative electrode fabric respectively;
[0047] The coagulation bath used is a solution that can cause component B in the composite polymer to undergo rapid physical crosslinking. For sodium alginate, it is a calcium chloride solution, and calcium ions can construct crosslinks between sodium alginate chain segments through electrostatic interactions; for chitosan, it is a sodium hydroxide solution, and the alkaline sodium hydroxide can neutralize the acid used to dissolve chitosan, causing the chitosan to re-crosslink and precipitate, and the electrode is solidified due to the crosslinking of the polymer.
[0048] Step 2: Printing and coating of gel electrolyte
[0049] (1) The components of the composite polymer in step 1 are also used, but the mass of component A is adjusted to 3 to 4 times the mass of component B, so that the electrolyte part has better ionic conductivity, and the solvent ratio is adjusted to 5 to 8 times the mass of the polymer, so that the gel electrolyte slurry has a certain fluidity, so as to achieve electrode wrapping, lithium sulfate is added to the slurry to a concentration of 1 to 2 mol / L, and after stirring until the polymer and lithium sulfate are dissolved, vapor-deposited hydrophilic nano-silica with a mass of one-tenth of the polymer is added, and the mixture is mixed evenly by a ball mill to obtain a gel electrolyte precursor for printing;
[0050] (2) using a 3D printer to print the gel electrolyte precursor on both sides of the electrode fabric using the same printing pattern and parameters as the electrode fabric, so that the printed gel electrolyte can cover and wrap the electrode fabric. During the printing process of the gel electrolyte, the ultraviolet light with a wavelength of 365 nm is continuously irradiated to crosslink the electrode fabric and component A in the gel electrolyte. The gel electrolyte is immediately solidified after wrapping the electrode, and the gaps between the mesh fabrics are retained;
[0051] (3) The printed, preliminarily formed gel electrolyte and the positive electrode fabric and negative electrode fabric wrapped therein are combined and immersed in a 2 mol / L lithium sulfate coagulation bath for 10 min. Component B in the gel electrolyte is cross-linked to form a whole. The gel electrolyte is then washed with a 2 mol / L lithium sulfate solution to ensure that the polymers in the electrode and electrolyte are completely cross-linked, other unreacted substances are washed away, and the lithium salt is fully and evenly infiltrated.
[0052] Step 3: Printing and packaging of energy storage fabric
[0053] (1) Mixing photocurable polyurethane acrylate and 4% photoinitiator 1173, adding the same mass of polyethylene glycol acrylate monomer as solvent, stirring and removing bubbles, and then transferring into the syringe of a 3D printer;
[0054] (2) Setting the printing extrusion speed to 2-3 mm3 / s and the printing travel speed to 3-6 mm / s, printing is performed on the front and back sides respectively, and ultraviolet light is irradiated during the printing process to encapsulate the battery in the outer layer of the gel electrolyte to obtain an energy storage fabric.
[0055] Example 1
[0056] According to the steps of the technical solution of the present invention, lithium permanganate is selected as the positive electrode active material, lithium titanium phosphate is selected as the negative electrode active material, component A in the composite polymer in the positive and negative electrodes and the electrolyte uses polyethylene glycol diacrylate, component B is chitosan, and light-cured polyurethane acrylate is used as the packaging material, and the energy storage battery fabric is gradually printed and prepared according to the method of the present invention. The specific capacity of the obtained energy storage battery fabric is calculated based on the mass of the positive electrode material to reach 98 mAh g -1 , and maintained 89% of the initial capacity after 50 cycles of charge and discharge.
[0057] Example 2
[0058] According to the steps of the technical solution of the present invention, the positive electrode active material is lithium iron phosphate, the negative electrode active material is lithium titanate, component A in the composite polymer in the positive and negative electrodes and the electrolyte is polyethylene glycol diacrylate, component B is sodium alginate, and light-cured polyurethane acrylate is used as the packaging material. The energy storage battery fabric is printed step by step according to the method of the present invention. The specific capacity of the energy storage battery fabric prepared by printing reaches 152mAh·g based on the mass of the positive electrode material. -1 , and has good wearable properties. It is breathable and flexible at the same time. Under 90° bending conditions, the charge and discharge cycle maintains 91% of the initial capacity.
[0059] The above contents are further detailed descriptions of the present invention in combination with specific implementation methods, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.
Claims
1. A method for preparing energy storage battery fabric by 3D printing, characterized in that The steps of this method are as follows: Step 1: Printing of electrode fabric (1) Using a composite polymer, multi-walled carbon nanotubes and nano-electrode active materials, mixing them in a mass ratio of 1:1:2, adding a solvent 5 to 10 times the mass of the solid, grinding or ball milling to dissolve and evenly disperse them to obtain a slurry for printing electrodes; The composite polymer is composed of a two-component polymer and a photoinitiator I2959, wherein component A is a photocurable polymer including polyethylene glycol diacrylate and polyethylene glycol dimethacrylate, and component B is a high-viscosity polymer that can be quickly physically cross-linked, including chitosan, sodium alginate and polyvinylidene fluoride; the mass of component A is 1 to 3 times the mass of component B; The active material is lithium iron phosphate particles or lithium permanganate particles for the positive electrode, and lithium titanate particles or lithium titanium phosphate particles for the negative electrode; The solvents used were deionized water for chitosan and sodium alginate and N-methylpyrrolidone for polyvinylidene fluoride; (2) After the bubbles are removed by ultrasound, the slurry used for printing the electrode is placed in the syringe of an extrusion direct writing 3D printer and printed in a grid pattern. The distance between the grid lines in the printed pattern is greater than or equal to 4 mm, and the extrusion speed during the printing process is 1 to 2 mm 3 / s, the printing speed is 2~5mm / s; (3) After printing, the copper and aluminum tabs are respectively inserted into the unshaped electrodes, and then immersed in a coagulation bath for 10 min until the polymer component B in the electrode is cross-linked and shaped, thereby obtaining positive electrode fabric and negative electrode fabric respectively; Step 2: Printing and coating of gel electrolyte (1) The components of the composite polymer in step 1 are also used, but the mass of component A is adjusted to 3 to 4 times the mass of component B, the solvent ratio is adjusted to 5 to 8 times the mass of the polymer, and lithium sulfate is added to a concentration of 1 to 2 mol / L. After the polymer and lithium sulfate are dissolved, vapor-deposited hydrophilic nano-silica with a mass of one-tenth of the polymer is added, and the mixture is mixed evenly in a ball mill to obtain a gel electrolyte precursor for printing; (2) using a 3D printer to print the gel electrolyte precursor on both sides of the electrode fabric using the same printing pattern and parameters as the electrode fabric, so that the printed gel electrolyte can cover and wrap the electrode network. During the printing process of the gel electrolyte, the ultraviolet light with a wavelength of 365 nm is continuously irradiated to crosslink the electrode fabric and component A in the gel electrolyte; (3) The printed preliminarily shaped gel electrolyte and the positive electrode fabric and the negative electrode fabric wrapped therein are combined and immersed in a 2 mol / L lithium sulfate coagulation bath for 10 min. Component B in the gel electrolyte is cross-linked to form a whole, and then washed with a 2 mol / L lithium sulfate solution; Step 3: Printing and packaging of energy storage fabric (1) Mixing photocurable polyurethane acrylate and 4% photoinitiator 1173, adding the same mass of polyethylene glycol acrylate monomer as solvent, stirring and removing bubbles, and then transferring into the syringe of a 3D printer; (2) Set the printing extrusion speed to 2-3 mm 3 / s, the printing speed is 3-6mm / s, printing is performed on the front and back sides respectively, and ultraviolet light is irradiated during the printing process. The battery is encapsulated in the outer layer of the gel electrolyte to obtain an energy storage fabric.
2. A method for preparing energy storage battery fabric by 3D printing according to claim 1, characterized in that: The viscosity of the slurry used for printing electrodes is 10 2 ~10 4 Pa·s, and the viscosity decreases with increasing shear rate. In addition, the storage modulus is higher than the loss modulus under low shear stress. After exceeding a certain shear stress, the storage modulus is lower than the loss modulus.
3. The method for preparing energy storage battery fabric by 3D printing according to claim 1, characterized in that: The coagulation bath used is a solution that can cause component B in the composite polymer to undergo physical crosslinking quickly, and is a calcium chloride solution for chitosan or a sodium hydroxide solution for chitosan.
4. A method for preparing energy storage battery fabric by 3D printing according to claim 1, characterized in that: After printing the gel electrolyte and printing the encapsulating photocurable polymer, due to the rapid cross-linking and curing, the polymer is wrapped to prevent the polymer from further flowing and blocking the holes in the grid electrode fabric, thereby retaining the air permeability of the fabric.
5. The method for preparing energy storage battery fabric by 3D printing according to claim 1, characterized in that: The prepared energy storage fabric has good flexibility due to the intrinsic flexibility of the electrodes, gel electrolyte and encapsulating polymer, and can maintain stable charging and discharging performance during bending.
Citation Information
Patent Citations
Method for preparing lithium ion battery stacked vertical crossed electrode based on 3D printing technology
CN104409690A
Method for preparing fabric-shaped aqueous lithium ion battery through screen printing technique
CN108054442A
Method of preparing solid-state lithium ion battery through photocuring 3D printing
CN110571475A
Manufacturing method of battery
JP2018060754A
